Comparative dosimetric analysis of whole abdominal radiotherapy with VMAT versus 3D conformal in patients with Wilms tumour. Issue 3 (15th February 2019) - Olmos, Alejandro; Rodriguez, Alejandro; Beltran, Estefania; Garay, Onix; Felix, Armando; Ponce, Mario Alberto; Salcedo, Maurico; Apresa, Teresa; Lio, Lorena; Guzman, Martha; Chilaca, Fatima
Abstract: Introduction: In this study, we undertake a dosimetric comparison of whole abdominal treatment plans of patients diagnosed with stage 3 Wilms tumour, to assess the benefits of treating these patients with volumetric arch therapy (VMAT) versus 3D conformal radiotherapy. Material and methods: A retrospective study was undertaken on 23 patients receiving either VMAT or 3D conformal radiotherapy during 2013–2017. A dosimetric comparison was undertaken for both techniques, measuring planning target volume (PTV), conformity index (CI), homogeneity index (HI) and organs at risk (OAR). Results: The dosimetric parameters for the PTV dose in the VMAT and 3D conformal technique showed no statistical difference (1, 289·17 cGy versus 1, 357·13 cGy, respectively, p =0·404). However, the VMAT technique had a better CI (1·04 VMAT versus 1·26 3D, p =0·004), and there was little difference in the HI (1·13 VMAT versus 1·15 3D, p =0·1606). In the statistical analysis, the decrease in dose to OAR for the VMAT technique is statistically significant for doses to lung and kidney ( p =0·011 and p =0·002, respectively). Between the two techniques, there was no statistical significance in dose difference to the other OAR. Conclusion: This work proposes using the VMAT technique in whole abdominal irradiation to improve conformity, without affecting the quality of the PTV coverage, when compared with the 3D conformal technique. In addition, VMAT reduces the doses to OAR such as the remaining kidney and lungs that are important to preserve to reduce the probability of radiation toxicity in these patients.